Taxation Revenue and Government Investment In Electricity: An Analysis of Indispensable Interconnection With VECM - Tajudeen Adejare Adegbite (Magister Akuntansi FB-UK.Maranatha, 2024)
This study appraised the effect of taxation on government investment in electricity in Nigeria. Data on electricity and taxation were realized through the ministry of works, power and housing as well as the CBN statistical Bulletins respectively from 1981 to 2022. The necessary data collected were experimentally analyzed with regression, VECM, and Cointegration analysis. Unit root test was also incorporated in this study for effective affirmation of stationary among the variables. Findings dispensed that taxation has positive effect on investment in electricity due to the fact that a percent upward movement of taxation significantly upsurge investment in electricity. Revenue from oil has positively affected investment in electricity insignificantly. Public debt has been notified having a negative significant effect on investment in electricity. Finally, government expenditure has been discovered having negative effect on investment in electricity in Nigeria. Conclusively, taxation has positive significant effect on the investment in electricity in Nigeria. The potency of electricity in improving economic status and enhancing people standard of living in Nigeria is indispensable which cannot be underestimated. It is therefore recommended that more devices should be made available to automatically allocate certain percentage from tax revenue for effective utilization on electricity investment in the country. Key Words: Electricity; Taxation; Oil revenue; government Expenditure; Public Debt